SARS-CoV-2 induces robust germinal center CD4 T follicular helper cell responses in rhesus macaques - Yashavanth Shaan Lakshmanappa; Sonny R. Elizaldi; Jamin W. Roh; Brian A. Schmidt; Timothy D. Carroll; Kourtney D. Weaver; Justin C. Smith; Anil Verma; Jesse D. Deere; Joseph Dutra; Mars Stone; Sergej Franz; et al. (Nature Communications, 2021)
Induction of CD4 T follicular helper (Tfh) cells is important for antibody responses to viral infections. Here, the authors show in a rhesus macaque model of mild COVID-19 that SARS-CoV-2 infection results in transient accumulation of proliferating Tfh cells with a Th1 profile in peripheral blood and generation of germinal center Tfh cells specific for viral proteins.